El bienestar social y el buen vivir: los olvidados en la toma de decisiones en materia económica - Koubi, Geneviève (2020)
The “buen vivir” designates a paradigm inherent to the social field which seeks to focus on human values such as solidarity and the model of sustainable development. In this sense, it differs from "living better" — an individualistic interpretation of life—, far from respecting the natural environment and which deifies the economic activity. Thus, this contribution aims to introduce a conceptual framework regarding «good living» to understand that the operational function of social welfare cannot be addressed in a unidimensional way, just considering the economy, but also environmental variables, such as public health, quality of life, social integration, access to social rights, among others. All this has an impact on the identification of indicators that also measure these variables, intending to allow all the people to be drivers in social, political, and economic development in a sustainable manner.